PENILAIAN PERTUMBUHAN HASIL BEBERAPA PERSILANGAN BENIH JAGUNG (ZEA MAYS) - Sembiring, Hendra Kurniawan; Alqamaril, Muhammad; Abd Rahman, Faizah Salvana; Yaseer Suhaimi Mohd, Yaseer Suhaimi; Maznan, Ahmad Firdaus (Jurnal Al Ulum LPPM Universitas Al Washliyah Medan, 2025)
Seed quality is the beginning of the success of a production process, corn germination test is needed so that this cross produces quality seeds. This research aims to determine the seed germination test carried. The research used a non-factorial randomized block design with 4 levels T1 (1 male :2 woman), T2 (Ratio 1 male :3 woman), T3 (Ratio 1male :4 woman), and T4 (Ratio 1male :5 woman). The germination percentage is calculated using the formula: germination percentage (%) = number of germinated seeds & number of seedsx100. The observations used are germination percentage, germination speed, germination index (G1), average seed germination (MGT) and normal and abnormal seed numbers. The results of the research showed that the percentage of corn seed germination in all replications showed the best results with seeds that grew in the range of 98%-100%. T1 (1 male: 2 females) showed the best speed of corn seed germination with 15.31 and the best average time of seed germination was shown in replicate T3 (1 male: 4 females) with an average of 3.74. The results showed that p < 0.05 was not significantly different in corn germination.